2022
DOI: 10.3233/jad-220043
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Social Cohesion and Dementia-Related Stigma Among Mothers of Adolescents in the Pre- and Current COVID-19 Period: An Observational Study Using Population-Based Cohort Data

Abstract: Background: Middle-aged adults may be the ideal target group for dementia-related stigma reduction interventions to encourage the utilization of services among those who may become family caregivers. Neighborhood social cohesion may diminish dementia-related stigma, particularly in terms of perceived public attitudes. The COVID-19 pandemic can further negatively impact perceived public stigma. Objective: To investigate the association between neighborhood social cohesion and dementia-related stigma during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Consequently, a lack of trust was related to the information spread by institutions such as the media and the government ( 21 ). For example, systemic discrimination and messaging from the government organizations, traditional news media ( 21 , 25 ), and online social media ( 27 ) were reported to heighten the intersection of dementia-related stigma and issues of racism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a lack of trust was related to the information spread by institutions such as the media and the government ( 21 ). For example, systemic discrimination and messaging from the government organizations, traditional news media ( 21 , 25 ), and online social media ( 27 ) were reported to heighten the intersection of dementia-related stigma and issues of racism.…”
Section: Resultsmentioning
confidence: 99%
“…Structural stigma was evident in the theme of cultural inequities and distrust among ethnic and racial minority groups of people living with dementia. For example, our review identified barriers related to systemic racism, discrimination, denied healthcare services, and inadequate culturally sensitive care ( 21 , 25 , 27 ). This finding is consistent with pre-pandemic research that indicates that structural stigma in the form of systemic racism and structural discrimination are entrenched in history and has been negatively impacting people with dementia from ethnic and racial minority groups ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wealth inequality loosens social cohesion 37. People with a higher wealth status had better social cohesion,38 which reduced stigma (maximise attitude) among people with chronic diseases 39. Thus, the higher the SES, the more social cohesiveness leads to better HIV service utilisation,40 which can improve attitude toward people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“… 37 People with a higher wealth status had better social cohesion, 38 which reduced stigma (maximise attitude) among people with chronic diseases. 39 Thus, the higher the SES, the more social cohesiveness leads to better HIV service utilisation, 40 which can improve attitude toward people living with HIV. Socioeconomic-related inequality was higher between women and men, but women had better comprehensive knowledge persistently.…”
Section: Discussionmentioning
confidence: 99%
“…These questions were selected to assess respondents' general attitudes toward PWD's social participation and explore their willingness to accommodate PWD. Explanatory variables were selected from past studies on stigma toward dementia, 5,7 and included experience with PWD, education on dementia, frequency of social contact with others, and trust for people in the community. Sex-stratified age groups, education, marital status, and other factors were also assessed (Supplementary File 1).…”
Section: Research Studiesmentioning
confidence: 99%